Biodegradable zwitterionic polymer membrane coating endowing nanoparticles with ultra-long circulation and enhanced tumor photothermal therapy. (February 2020) - Peng, Shaojun; Ouyang, Boshu; Men, Yongzhi; Du, Yang; Cao, Yongbin; Xie, Ruihong; Pang, Zhiqing; Shen, Shun; Yang, Wuli
Abstract: Long blood circulation is the basic requirement of advanced drug delivery systems for tumor treatment, which leads to enhanced tumor therapeutic efficiency and reduced side effects. However, the pharmacokinetics of the current nanoparticles in vivo is still unsatisfactory, which leads to limited success to translate nanoparticles into clinical applications. Inspired by the natural cell membrane-coating strategy, a series of zwitterionic polymer membranes are firstly developed and coated onto different kinds of nanoparticles in this work. Intriguingly, the zwitterionic polymer membrane shows stronger protein adsorption resistance and reduced macrophage uptake compared with the corresponding zwitterionic polymer brush or the red blood cell (RBC) membrane, which results in longer blood circulation time and higher tumor accumulation of the coated nanoparticles. Combined with the photothermal effect of model nanoparticles, Fe3 O4, zwitterionic polymer membrane-coated Fe3 O4 shows enhanced photothermal therapy (PTT) efficacy on A549 tumors compared with the corresponding zwitterionic polymer brush or RBC membrane-coated Fe3 O4 . Notably, Fe3 O4 coated by carboxybetaine-based biomimic membranes exhibits the ultra-long blood circulation ( t 1/2 = 96.0 h) and strongest PTT efficacy compared with those coated by phosphorylcholine-based or sulfobetaine-based biomimic membranes. In addition, the zwitterionic biomimic membrane exhibits rapid glutathione-triggered degradation with the products of low molecular weight (<2000 g mol −1 ). Therefore, the biodegradable zwitterionic biomimic membrane coating offers a universal platform for the design and application of long-circulating biomedical nanoparticles, which may pave the way for the clinical applications of biomedical nanoparticles in tumor therapy.